2001
DOI: 10.1309/0kpe-1rg6-ka78-r49y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrothermal Cautery-Assisted Resection of Diminutive Colonic Polyps on Histopathologic Diagnosis

Abstract: We examined diminutive colonic polyps to identify relationships between thermal electrocoagulation or resection trauma cytologic artifacts, type of thermal electrocoagulation, polyp size, and the interobserver variation among 3 pathologists. The 3 pathologists independently evaluated 119 colonic polyps 5 mm or less in maximum dimension for diagnosis and degree of thermal electrocoagulation or resection trauma cytologic artifacts. The maximum dimension of the polyps and type of thermal electrocoagulation were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
1
16
0
1
Order By: Relevance
“…In the treatment of small polyps with hot forceps polypectomy, it can be difficult to assess the histologically definitive diagnosis of polyps due to cautery artifacts (9,10). In the study by Goldstein et al (9), it was reported that the average percentage of polyps in which a definitive diagnosis could not be made because of cytologic artifacts was 16.5% (range, 11.8%-19.3%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment of small polyps with hot forceps polypectomy, it can be difficult to assess the histologically definitive diagnosis of polyps due to cautery artifacts (9,10). In the study by Goldstein et al (9), it was reported that the average percentage of polyps in which a definitive diagnosis could not be made because of cytologic artifacts was 16.5% (range, 11.8%-19.3%).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Goldstein et al (9), it was reported that the average percentage of polyps in which a definitive diagnosis could not be made because of cytologic artifacts was 16.5% (range, 11.8%-19.3%). The same study reported that polyps smaller than 2 mm were significantly less likely to be definitively diagnosed because of cautery artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first to describe ESD-related nuclear artifacts in detail. Nuclear artifacts were found close to marking-related erosive and/or depressed coagulation, corresponding to thermal artifacts, also called electrothermal, diathermic, or cautery-related changes (1,3,4,(9)(10)(11). Therefore, nuclear artifacts themselves would have contributed to the thermal artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The precise histological assessment of ER specimens, such as pathological diagnosis, the depth of cancerous invasion, lymphovascular permeation and the status of the surgical margin, is crucial for the subsequent management of the patients (1,3,4,(6)(7)(8)(9). Therapeutic procedures using electrothermal devices may induce varying artifacts disturbing the histological evaluation in gastrointestinal and other specimens (1,3,4,(9)(10)(11)(12)(13)(14). However, histological artifacts in newly developed ESD specimens remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although HBF has the advantages of fulgurating any adenomatous remnants, and coagulating blood vessels, it has several drawbacks related to electrocautery, such as perforation and delayed bleeding [4,5]. In addition, some prospective studies have demonstrated that the cytological features of DCPs can be distorted by thermal electrocoagulation-induced cytological artifacts, so that a definitive diagnosis cannot be made [6].…”
Section: Introductionmentioning
confidence: 99%